Potential Role of Endogenous Adenosine in Ticagrelor‐Induced Dyspnea. Issue 8 (26th May 2013) - Belchikov, Yuly G.; Koenig, Seth J.; DiPasquale, Elissa M.
<x xml:space="preserve">Abstract</x> Ticagrelor, a recently approved platelet antagonist indicated for the reduction of thrombotic cardiovascular events in patients with acute coronary syndrome (ACS), has been reported to cause dyspnea in more than 13% of patients. Dyspnea is not a clinically relevant adverse event with other medications indicated for ACS. One suggested mechanism of ticagrelor‐induced dyspnea involves an increase in systemic adenosine concentrations through adenosine deaminase inhibition. Dyspnea, a subjective finding resulting from physiologic and sensory mechanisms, may be a consequence of increased systemic adenosine concentrations, leading to amplified and prolonged receptor activity. Current literature suggests, however, that pulmonary status is not compromised, with no reduction of efficacy seen in patients with ticagrelor‐induced dyspnea, thus allowing clinicians to continue therapy without reservation. Still, patients with a history of asthma and chronic obstructive pulmonary disease may be more susceptible to ticagrelor‐induced dyspnea, potentially leading to nonadherence and exacerbations of morbidity. Therefore, it is paramount that health care providers continually monitor these patients with the aims of maintaining medication therapy adherence and providing relevant options if dyspnea becomes intolerable.